Experimental Test of Ignition Timing with Programable CDI on Performance Single Cylinder Otto Engine - Rachmanto, Rendy Adhi; Wijayanto, Martinus Darmawan Bagas; Juwana, Wibawa Endra; Kataraki, Pramodkumar Siddappa (Universitas Sebelas Maret, 2022)
Ignition timing is sparking from the spark plug based on the ignition angle during the compression stroke in the combustion chamber relative to the piston position and the crankshaft angular speed. Adjusting the ignition angle is one method to optimize the combustion process in the engine. An optimal combustion process can improve engine performance and reduce fuel consumption. This study investigates optimal data from ignition angle changes using a programmable Capacitive Discharge Ignition (CDI). The test was performed on a single-cylinder four-stroke Otto engine with standard ignition angle variations, +3°, +6°, and +9° before Top Dead Centre (TDC). The test results show that torque and power have increased while brake-specific fuel consumption has decreased. Optimal data acquisition at ignition angle of +9° with peak torque value of 6.91 Nm and peak power value of 4.80 kW, while the lowest value of specific fuel consumption is 0.234 kg/kWh, and the highest value of thermal efficiency is 36%. From this study, it was concluded that the ignition timing could affect the engine performance.